Pendampingan Pengtembangan Bahan Ajar Sejarah Makanan Tradisional Kudus - Imaniar Purbasari; Nur Fajrie (Muria Jurnal Layanan Masyarakat, 2019)
Local cultural elements that have a high attractiveness to be developed in traditional foods bussines. Traditional food has an identity attached to the ingredient used. Indonesia has traditional food, one of which is soto. Foods with yellow gravy which is equipped with side dishes and vegetables are of various types in all corners of Indonesia. Kudus has a religious city identity with a history of acculturation oh Hinduism and Islam, soto Kudus with the ingredients of buffalo meat as its side dish. The traditional food philosophy is explored to find the socio-cultural aspects of food distory, nutritional value, and the development of traditional foods. The findings are aimed at the world of education, especially children so that the attachment of local cultural elements becomes a priority of life in the digital era.